COVID-lockdown in English higher education March–June 2020. Were disabled students' needs forgotten?. (3rd July 2022) - Newman, Ivan
ABSTRACT: The COVID-19 pandemic forced HE Providers (HEPs) to radically transition traditional teaching and assessment to 100% remote delivery. UK Governments' policies widening HE participation have yielded a significant minority of disabled students (15%). This study investigated English HEPs ( n = 133) transition advice to academics regarding these students' needs. Of 104 respondents, 16% provided new advice regarding remote teaching for disabled students, 22% regarding remote assessment; only 2 mentioned they had conducted Equality Impact Assessments (EIAs) about the changes. Disabled students' needs appear forgotten. Four response models were identified: Keep Calm and Carry On, Meet an Existential Threat, All Hands to the Pumps, An Opportunity for Change. Emergent good practice examples are given. Most English HEPs should urgently conduct EIAs under their legal Anticipatory Public Sector Equality Duty. The whole sector needs to better institutionalise delivering to disabled students' needs through effective inclusivity policy implementation, and educating academics and academic management.